Phosphatic condition of the light gray forest soil at introduction of the increasing doses of afteralcohol grains - N. A. Korchenkina; E. V. Dabakhova; V. I. Titova (Аграрная наука Евро-Северо-Востока, 2017)
For the purpose of an assessment of transformation of a phosphatic condition of the light gray forest soil under action of afteralcohol grains in the laboratory of the department of agrochemistry and agroecology of the Nizhny Novgorod SAA carried out an experiment by laying the model experience. As the studied factor are taken increasing doses of afteralcohol grains which in production conditions conventionally correspond to doses of 50, 100, 150 and 200 m3/ha. The fractional composition of phosphates in the soil was determined right after laying of experience, and then every 2 week for 3 months. As the object of research used waste produced in the technological cycle of "Distillery" Chugunovsky" Vorotynsky district of Nizhny Novgorod, containing in the structure 3,7% of solid, 0,44% of nitrogen, 0,06% of phosphorus and 0,12% of potassium. During researches it is established that with increase in a dose of afteralcohol grains making the absolute content and a share of organic phosphorus in relation to gross increases. The total of mineral phosphates on the fertilized options is higher, than on control, however their individual share in the general reserves of phosphorus at increase in a dose of afteralcohol grains decreases by 3%. The sum of phosphates of all groups at introduction of the increasing doses afteralcohol grains an comparison with control option increases - by the end of experience their contents on option with the maximum dose of afteralcohol grains in comparison with control option increases from 35 up to 42%. At the same time it is noted that increase of content of phosphates is reached due to increase in amount of less valuable phosphates of iron and aluminum in the agronomical relation. The unidirectional tendencies in dynamics of a phosphatic condition of the soil during the studied period aren't revealed. Use of high doses of afteralcohol grains promotes essential (to 50%) to increase of fosfatazny activity of the soil.